MORAL ANDETHICAL DIMENSIONECOLOGICALKNOWLEDGE - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The articlediscussesthe featuresand trends of thedevelopmentof a newbranchof human knowledge – environmental ethics.